Morphological and molecular description of Ixodes woyliei n. sp. (Ixodidae) with consideration for co-extinction with its critically endangered marsupial host. Issue 1 (December 2017) - Ash, Amanda; Elliot, Aileen; Godfrey, Stephanie; Burmej, Halina; Abdad, Mohammad; Northover, Amy; Wayne, Adrian; Morris, Keith; Clode, Peta; Lymbery, Alan; Thompson, R.
Abstract Background Taxonomic identification of ticks obtained during a longitudinal survey of the critically endangered marsupial, Bettongia penicillata Gray, 1837 (woylie, brush-tailed bettong) revealed a new species ofIxodes Latrielle, 1795. Here we provide morphological data for the female and nymphal life stages of this novel species (Ixodes woyliei n. sp.), in combination with molecular characterisation using the mitochondrial cytochromec oxidase subunit 1 gene (cox 1). In addition, molecular characterisation was conducted on several describedIxodes species and used to provide phylogenetic context. Results Ixodes spp. ticks were collected from the two remaining indigenousB. penicillata populations in south-western Australia. Of 624 individualB. penicillata sampled, 290 (47%) were host to ticks of the genusIxodes ; specificallyI. woyliei n. sp., I. australiensis Neumann, 1904, I. myrmecobii Roberts, 1962, I. tasmani Neumann, 1899 andI. fecialis Warburton & Nuttall, 1909. Of these, 123 (42%) were host to the newly describedI. woyliei n. sp. In addition, 268 individuals from sympatric marsupial species (166Trichosurus vulpecula hypoleucus Wagner, 1855 (brushtail possum), 89Dasyurus geoffroii Gould, 1841 (Western quoll) and 13Isoodon obesulus fusciventer Gray, 1841 (southern brown bandicoot)) were sampled for ectoparasites and of these, I. woyliei n. sp. was only found on twoI. o. fusciventer. Conclusions Morphological and molecular data have confirmed the first new AustralianIxodes tick species described in over 50 years, Ixodes woyliei n. sp. Based on the long-term data collected, it appears this tick has a strong predilection forB. penicillata, with 42% ofIxodes infections on this host identified asI. woyliei n. sp. The implications for this host-parasite relationship are unclear but there may be potential for a future co-extinction event. In addition, new molecular data have been generated for collected specimens ofI. australiensis, I. tasmani and museum specimens ofI. victoriensis Nuttall, 1916, which for the first time provides molecular support for the subgenusEndopalpiger Schulze, 1935 as initially defined. These genetic data provide essential information for future studies relying on genotyping for species identification or for those tackling the phylogenetic relationships of AustralianIxodes species.